2017
DOI: 10.1007/s00404-017-4504-8
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term reliability of fractioned CO2 laser as a treatment for vulvovaginal atrophy (VVA) symptoms

Abstract: Long-term data showed that the improvement of vaginal health may continue up to 24 months after fractional CO laser treatment although between 18 and 24 months benefits decline, and approximately 80% of women decide to start a new treatment cycle of laser applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 13 publications
0
32
0
Order By: Relevance
“…A total of 24 clinical studies were identified that investigated transvaginal LASER in women with GSM/VVA. Two studies appeared to include the same study population (separate analyses) .…”
Section: “Genitourinary Syndrome Of Menopause” and Vaginal Atrophymentioning
confidence: 99%
“…A total of 24 clinical studies were identified that investigated transvaginal LASER in women with GSM/VVA. Two studies appeared to include the same study population (separate analyses) .…”
Section: “Genitourinary Syndrome Of Menopause” and Vaginal Atrophymentioning
confidence: 99%
“…The laser treatment program includes three cycles 30-40 days apart as attack therapy, with one cycle per year as maintenance therapy, although data on duration and frequency of maintenance therapy are discordant. Gambacciani et al [41] reported positive results for at least 12 months while Pierrali et al [42] observed a decline in patient satisfaction, from 76% to 52%, 3-25 months after the last procedure. This implies that the effect of the procedure is time-dependent and should be repeated.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are no long- term data to support current recommendations. 1013 Laser therapy is not available on the NHS and treatments are expensive, averaging £700.00 per treatment. Many women with the potential to benefit will be unable to afford this option.…”
Section: Treatment Optionsmentioning
confidence: 99%